Nonlinear Propagation of Sectoral Productivity Shocks with Variable Elasticities of Substitution - Saumik Paul; Dhushyanth Raju (Institute of Labor Economics (IZA), 2023)
This paper examines the nonlinear propagation of sectoral productivity shocks in a general equilibrium framework with intersectoral linkages characterized by allowing elasticities of substitution in sectoral outputs and sectoral productivities to vary across sector pairs. Evidence based on a sample of 38 countries and 35 sectors shows stronger roles of certain sectors in the aggregate propagation of sectoral productivity shocks with variable elasticities than with constant elasticities. The results of sectoral productivity shocks on cross-country income convergence between 2005 and 2011 are robust across the two types of elasticities in terms of the direction of change, but not the magnitude.
Keywords: D24; F15; F43; N10; O47; D57; Q54; 330; nonlinear propagation of productivity shock; Morishima elasticity of substitution; intersectoral linkages